KESULITAN GURU MEMBUAT MEDIA PEMBELAJARAN DI SDN 01 MUARA TAIS TIMUR, KABUPATEN PASAMAN - Risva, Nefita; Dafit, Febrina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the difficulties experienced by teachers in creating learning media at SDN 01 Muara Tais Timur, Pasaman Regency. This study used a qualitative case study approach. The research informants consisted of teachers in grades IV, V, and VI. Data collection techniques were conducted through observation and interviews. Data analysis was conducted through data reduction, data presentation, and drawing conclusions. The results indicate that teachers' difficulties in creating learning media are influenced by internal and external factors. Internal factors include teachers' lack of knowledge and skills in creating learning media, time constraints, age, and teachers' habits and comfort with teaching without using learning media. External factors include the suboptimal utilization of available facilities and infrastructure at the school and the lack of training or workshops on creating learning media.